Interior textiles : design and developments - Rowe, T. (Trevor) (Woodhead publishing in textiles, 2009)
This book provides an overview of the types of textiles used within the interior textile sector and key technological developments and safety issues affecting the industry. An understanding of these topics enables the designer or manufacturer to select the most appropriate fabrics for interior applications. The first group of chapters reviews types and selection of materials for interior textiles, including natural and synthetic fibres as well as knitted, woven and nonwoven fabrics. Further chapters review surface design of interior textiles and the use of textiles in carpets and floor coverings. The second part of the book discuses developments in such areas as joining furniture fabrics, the use of sustainable and recycled textiles in interior applications, using interior textiles to minimise indoor environmental pollution, flame retardant materials and innovative textiles for seating. Interior textiles: design and developments is an important text for manufacturers, designers and buyers of interior textiles as well as being a valuable resource for students and academics studying interior design and materials. Provides a comprehensive review of the type of textiles used within the interior textile sectorConsiders environmental issues in interior textiles assessing different types of sustainable and recycled textilesExplores the important issues of surface design and flammability testing.